2020
DOI: 10.3390/w12092497
|View full text |Cite
|
Sign up to set email alerts
|

High Loaded Bioflocculation Membrane Reactor of Novel Structure for Organic Matter Recovery from Sewage: Effect of Temperature on Bioflocculation and Membrane Fouling

Abstract: The effect of temperature on the efficiency of high loaded bioflocculation membrane reactor (HLB-MR) flocculation and concentration of organic matter in municipal wastewater was analyzed using parallel comparative experiments. The study investigated organic matter recovery efficiency, bioflocculation effect, and membrane fouling status of the reactor at 8 °C and 15 °C. It was observed that at a low temperature of 8 °C, the organic matter recovery efficiency of HLB-MR was 80%, which was equivalent to that at 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In particular, for the UF1 membrane, some macromolecules with variable size and different shape could be able to clog the pores of the membranes in various ways. It is reported that calcium cations display a bio-flocculation effect in carbohydrates, fats, and proteins ( Wan et al, 2020 ) and thus such agglomerated molecules may cause the obstruction of the membrane ( Alazmi et al, 2010 ). In this way, the carbohydrates from Nejayote probably bio-flocculated due to the presence of calcium hydroxide On the other hand, it has been reported that calcium ions can create a layer of incrustations in UF membranes, causing a permeate flux decrease depending on the ion concentration and the operating time ( Prisciandaro et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, for the UF1 membrane, some macromolecules with variable size and different shape could be able to clog the pores of the membranes in various ways. It is reported that calcium cations display a bio-flocculation effect in carbohydrates, fats, and proteins ( Wan et al, 2020 ) and thus such agglomerated molecules may cause the obstruction of the membrane ( Alazmi et al, 2010 ). In this way, the carbohydrates from Nejayote probably bio-flocculated due to the presence of calcium hydroxide On the other hand, it has been reported that calcium ions can create a layer of incrustations in UF membranes, causing a permeate flux decrease depending on the ion concentration and the operating time ( Prisciandaro et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%